Vection in depth during consistent and inconsistent multisensory stimulation in active observers - Ash, April (University of Wollongong, 2013)
The study of visual illusions of self-motion, or vection, has a long history of research dating back to its first descriptions by Helmholtz (1867). Early vection studies tended to induce vection in stationary observers or passively moved observers (externally generated perceptions of self-motion). It has not been until recently that studies have examined this experience in actively moving observers (self-generated perceptions of self-motion). With continuing advances in technology, it has become increasingly more important to understand the perception of self-motion in active observers where there is some interaction between the observer and the virtual visual environment. This thesis consists of four experimental chapters. These chapters examined the effect of consistent and inconsistent multisensory self-motion stimulation (compared to stationary vision-only self-motion situations) on the strength of vection in depth during active seated head movements (Empirical Chapters 1-3) and during treadmill walking (Empirical Chapter 4). In addition, this thesis examined the robustness of the viewpoint jitter and oscillation advantage for vection (compared to non-jittering constant velocity optic flow) under different self-motion situations and contexts. Overall, both vection in depth and the viewpoint jitter/oscillation advantage were remarkably tolerant to inconsistent multisensory self-motion situations; however, consistent visual-vestibular information was shown to increase vection compared to vision-only conditions in some seated self-motion situations. Together, the findings of this thesis suggest that multisensory interactions during vection are more complicated than originally thought and depend on a number of factors - including the physical/simulated axis of self-motion, the type and level of multisensory conflict and the type and number of senses involved. Specifically, this thesis showed that: (i) consistent horizontal (but not depth) visual-vestibular information during active seated head movements increased vection in depth compared to vision-only conditions; and (ii) biomechanical information about self-motion during treadmill walking globally reduced vection in depth compared to vision-only conditions. However, despite overall reductions during treadmill walking, there was always a viewpoint jitter and oscillation advantage for vection.
Keywords: Riecke_supervised_thesis; multi-modal vection; supervisedThesis